Valuation and investment appraisal - Geddes, Ross (Kent : Financial World, 2002)
Focuses on the evaluation of investment decisions, by highlighting the key elements of financial statements and the ratios therein and their relevance to the financial analyst in the valuation of companies.
Includes index.
oif 19/03/15
Loans
Keywords: Real property; Investments; Valuation; Real estate; Real estate investment; Great Britain